2014
DOI: 10.1186/0717-6287-47-23
|View full text |Cite
|
Sign up to set email alerts
|

Compositional studies and biological activities of some mash bean (Vigna mungo (L.) Hepper) cultivars commonly consumed in Pakistan

Abstract: BackgroundIn recent years, the desire to adopt a healthy diet has drawn attention to legume seeds and food products derived from them. Mash bean is an important legume crop used in Pakistan however a systematic mapping of the chemical composition of mash bean seeds is lacking. Therefore seeds of four mash bean (Vigna mungo (L.) Hepper, family Leguminoseae) cultivars (NARC-Mash-1, NARC-Mash-2, NARC-Mash-3, NARC-Mash-97) commonly consumed in Pakistan have been analyzed for their chemical composition, antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 33 publications
2
76
0
Order By: Relevance
“…Our result indicated that inclusion of soybean oil in feed does not compromise the species growth, suggesting the possible replacement of fish oil with soybean oil in diet formulation for darkbarbel catfish. The positive relationship between tissue fatty acid composition and dietary fatty acid contents has been well demonstrated in previous studies (Bransden et al, 2005;Zia-Ul-haq et al, 2007a, b, 2008, 2011aLuo et al, 2008;Rezek et al, 2010). In this study, the muscle fatty acid composition in fish generally reflected the lipid composition in diets similar to the report of Ng et al (2003) that the high fatty acids in feed can lead to high fatty acids in muscle.…”
Section: Discussionsupporting
confidence: 71%
“…Our result indicated that inclusion of soybean oil in feed does not compromise the species growth, suggesting the possible replacement of fish oil with soybean oil in diet formulation for darkbarbel catfish. The positive relationship between tissue fatty acid composition and dietary fatty acid contents has been well demonstrated in previous studies (Bransden et al, 2005;Zia-Ul-haq et al, 2007a, b, 2008, 2011aLuo et al, 2008;Rezek et al, 2010). In this study, the muscle fatty acid composition in fish generally reflected the lipid composition in diets similar to the report of Ng et al (2003) that the high fatty acids in feed can lead to high fatty acids in muscle.…”
Section: Discussionsupporting
confidence: 71%
“…However, these results showed that Elrashad seeds contained reasonable levels of most essential amino acids. The results of this study were comparable to the results produced by previous studies on amino acid composition of L. sativum (Gokavi et al, 2004;Zia-Ul-Haq et al, 2011). Young & Pellet (1994 concluded that the essential amino acid levels found in plant proteins deserve further consideration.…”
Section: Fatty Acid Compositionsupporting
confidence: 82%
“…It was not a surprise that all samples were specially rich in total catechins as these compounds are the major phenolic group in tea infusions, accounting for 40% of total water-soluble solids in tea infusions [4]. e content of total catechins was higher than the content of total phenols, and although this behavior is very rare, it has been reported previously in some legumes by Xu and Chang [27] and Zia-Ul-Haq et al [28]. e explanation of this behavior is that acid treatment of vanillin-HCl method has an effect on depolymerization of catechins, and they are quantified in more quantity than the phenolics quantified by Folin-Ciocalteu method where phenolics are not depolymerized.…”
Section: Nutraceutical Propertiesmentioning
confidence: 83%